Working capital management and financial performance: empirical study of listed manufacturing companies in sri lanka. - Sinthuja, N.; Hemaluxjini, T. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
Working capital management is a very essential component of corporate finance because it directly affects the liquidity and profitability of the firm and it is a key factor in determining financial performance of the firms. A firm is required to maintain a balance between liquidity and profitability while conducting its day to day operations. Liquidity is a precondition to ensure that firms are able to meet its short-term obligations and its continued flow can be guaranteed from a profitable venture. Therefore working capital management concept is important to fund the difference between short-term assets and short-term liabilities. This study is to investigate the relationship between working capital management and financial performance of listed Manufacturing companies in Sri Lanka. For the purpose of this study 28 listed manufacturing firms in Colombo stock exchange were incorporated as sample. The Data were collected from firm’s annual reports over the period of 2011 to 2017 from the CSE website. Cash conversion cycle, current ratio and current liabilities to total assets ratio used to measure the working capital management whereas return on assets used to measure financial performance. The hypotheses are examined by using correlation analysis and regression analysis. The overall result reveals that there is a significant relationship between working capital management and financial performance.
Keywords: Working Capital Management; Performance; Cash Conversion Cycle; Return on Asset